Redescription of Chrysaora lactea Eschscholtz, 1829 (Cnidaria, Scyphozoa) from the Brazilian coast, with designation of a neotype - Morandini, André C.; Da Silveira, Fábio L.; Cornelius, Paul F.s. (Zootaxa, 2006)
A redescription of the species Chrysaora lactea from the western South Atlantic is given based on live and preserved specimens from the Brazilian, Uruguayan and Argentinean coasts, and a neotype specimen is designated. The species is one of the commonest scyphomedusae in Brazilian coastal waters, reaching up to 25 cm in bell diameter with several different colour patterns (mainly milkywhite). The species is recorded with certainty from Jamaica to the northern coast of Argentina, and can be distinguished from its congeners primarily by the order of the development of tentacles (2nd, 3rd, 1st, 3rd, 2nd).